Flash report on evaluation of tomato and capsicum candidate lines for registration in Tanzania - Schafleitner, R. (International Food Policy Research Institute, 2023)
Background The trials were conducted in three regions: Kilimanjaro, Arusha, and Iringa. They comprised nine (9) lines of tomatoes with three (3) local checks, six (6) lines of chilies with one local check, six (6) lines of Habanero with one local check, and six (6) lines of sweet peppers with one local check. The primary goal of this project is to enhance vegetable production in Tanzania by developing new and improved varieties of tomatoes, sweet peppers, and habanero peppers. This will be accomplished through the following steps: 1. Assessing breeding lines of tomatoes, sweet peppers, and habanero peppers in various agroecological zones. 2. Conducting participatory variety selection of the chosen lines. 3. Applying the Distinctive, Uniformity, and Stability (DUS) test to the selected materials as part of the variety registration process.